[INVITED] Novel optical biosensing technologies for detection of mycotoxins. (January 2019) - Nabok, A.; Al-Rubaye, A.G.; Al-Jawdah, A.M.; Tsargorodska, A.; Marty, J.-L.; Catanante, G.; Szekacs, A.; Takacs, E.
Highlights: Total internal reflection ellipsometry (TIRE) was the main optical detection method. LSPR transducers were produced by annealing of thin gold films, then functionalized with half-antibodies or aptamers. The LSPR/TIRE combination allows the detection of mycotoxins in low concentrations (10 ppt). Optical planar waveguides is the way forward to development of highly sensitive and portable biosensors. Polarization interferometer sensor-prototype enables detection of mycotoxin in ppt concentrations. Abstract: This work reviews our recent progress in development of novel optical methods of detection of mycotoxins in direct assay with either specific antibodies or aptamers. The main method in this work was the total internal reflection ellipsometry (TIRE) combined with LSPR transducers based on gold nano-structures produced by annealing of thin gold films. The gold nano-islands produced were characterised with SEM, AFM, UV–visible absorption spectroscopy, and spectroscopic ellipsometry. The combination of TIRE and LSPR offers superior refractive index sensitivity as compared to traditional UV–vis absorption spectroscopy. The limitations of LSPR related to a short evanescent field decay length can be overcome using small-size bio-receptors, such as half-antibodies and aptamers. The achieved sensitivity of detection of mycotoxins in 0.01 ppb level of concentration is sufficient for the use of this method for analysis of agriculture products, food and feed on the presence of mycotoxins. Even higher sensitivity in sub-ppt level was achieved with another optical biosensor developed recently; it is based on optical planar waveguide operating as polarization interferometer (PI). This method is promising for development of portable, highly sensitive, and simple to use biosensors suitable for point-of-need detection of mycotoxins.